2019
DOI: 10.1111/ppc.12375
|View full text |Cite
|
Sign up to set email alerts
|

Do university students' personality traits affect their attitudes towards gender roles?

Abstract: Purpose Attitudes of individuals towards gender roles may be affected by their experiences such as personality traits. This study is to identify the relationship between university students' personality traits and their attitudes towards gender roles. Design and Methods This cross‐sectional was conducted with 301 university students between November 2018 and January 2019. Findings The students who had introverted personality traits had traditional attitudes according to the egalitarian gender role subscale (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…This study revealed that nursing students have an egalitarian gender role attitude in all areas, including social, family, and employment functions, similar to other studies in the literature 9,35–37 . However, it was observed that the nursing students displayed a less egalitarian attitude in the employment area compared to the family and social area.…”
Section: Discussionsupporting
confidence: 87%
“…This study revealed that nursing students have an egalitarian gender role attitude in all areas, including social, family, and employment functions, similar to other studies in the literature 9,35–37 . However, it was observed that the nursing students displayed a less egalitarian attitude in the employment area compared to the family and social area.…”
Section: Discussionsupporting
confidence: 87%
“…The studies conducted in Turkey and Africa to determine gender roles of university students, have demonstrated that female students have a higher level of positive thinking regarding gender equality compared to male students. 5 , 12 - 14 In another study conducted with medical students in Pakistan it was revealed that female students were exposed to gender discrimination more often. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Nursing students are expected to develop an egalitarian attitude towards gender and to help shape the societies in which they are providing care. 8 This study thus aimed to determine the attitudes towards gender equality of nursing students studying at a private university, the socio-demographic factors affecting gender equality, and the difference in perspectives towards gender between Turkish and foreign students.…”
Section: Introductionmentioning
confidence: 99%